The New Oceanographic Equipment of the "D’Entrecasteaux" - Le Gouic, Michel (The International Hydrographic Review, 2015)
The D’ENTRECASTEAUX is SHOM’s most important vessel. She began her active service 25 years ago, and her specific equipment has evolved in line with technological developments. In particular, in 1994, she was equipped with two systems enabling her to make oceanographic investigations while underway. These are an Acoustic Doppler hull-mounted Current Profiler (ADCP) by means of which current profiles over an 800-metre section can be obtained, and a towed vehicle (Sea Soar), able to oscillate between Om and 400m depths, which can carry sensors such as a CTD probe or a fluorimeter. This article evaluates the present surveying capacity of the D’ENTRECASTEAUX, with regard to hydrography, geophysics and oceanography and presents, in particular, her two new items of oceanographic equipment: the ADCP and the Sea Soar.